Comparison of high antioxidant ZnONPs produced from different fungi as alternative biomaterials - Mohanad Fawzi Mutar Mutar; Olcay Gençyılmaz (International Journal of Secondary Metabolite)
In this study, zinc oxide nanoparticles (ZnONPs), a promising alternative biomaterial, were synthesized using a non-toxic, cost-effective green synthesis approach using various fungal species (Penicillium citrinum, Fusarium solani, Aspergillus flavus and Aspergillus niger). The effect of different fungal species on the structural, optical, morphological and antimicrobial properties of ZnO nanoparticles (ZnONPs) was compared. ZnO nanoparticles (ZnONPs) crystallized in a hexagonal wurtzite structure with grain sizes ranging from 45 to 61 nm. Fungal species had a significant effect on the surface plasmon resonance (SPR) peak observed at 302 nm. ZnONPs were obtained in different morphologies such as nanodiscs, nanospheres, nanorchins and nanonuts, and it was determined that fungal species had a significant effect on these structures. The antibacterial activity of ZnONPs against Candida albicans, Streptococcus mutans, Pseudomonas aeruginosa, Eosinophilic pneumonia and Staphylococcus aureus was investigated. The effect of these nanoparticle shapes on antibacterial activity was evaluated. ZnONPs were found to have a significant antimicrobial effect especially on Candida albicans and Streptococcus mutans. ZnONPs produced only with Aspergillus niger fungus were found to have a strong antimicrobial effect especially on Staphylococcus aureus. Based on these results, the biosynthesis of ZnO nanoparticles (ZnONPs) using Penicillium citrinum, Fusarium solani, Aspergillus flavus and Aspergillus niger fungal species is proposed for the production of ZnONPs as a biomaterial with remarkable antibacterial properties and various morphologies.